TECHNOLOGY OF MISCANTHUS BIOMASS SACCHARIFICATION WITH COMMERCIALLY AVAILABLE ENZYMES - T. N. Goryachkovskaya; K. V. Starostin; I. A. Meshcheryakova; N. M. Slynko; S. E. Peltek (Вавиловский журнал генетики и селекции)
We analyzed the possibility of using commercially available enzymes with cellulosolytic activity for saccharification of miscanthus biomass, Soranovsky variety, a new crop registered in Russia in 2013, in comparison to the saccharification of biomasses of Phalaris arundinacea, Thrachomitum lancifolium, and Sida hermaphrodita. For enzymatic hydrolysis, we used commercially available fungal cellulases: Thermomyces lanuginosus xylanase, Aspergillus niger cellulase, and Pen. verruculosum cellobiase and cellulase. A biomass was ground and incubated in alkaline peroxide. The highest rate of hydrolysis was observed with the Phalaris arundinacea biomass. We tested various combinations of enzymes and achieved 100 % conversion for all samples relative to the weight of hydrolyzable components, which corresponds to 70 % conversion of biomass.